2013
DOI: 10.1007/s11538-013-9893-7
|View full text |Cite
|
Sign up to set email alerts
|

A Stronger Necessary Condition for the Multistationarity of Chemical Reaction Networks

Abstract: To cite this version:Sylvain Soliman. A stronger necessary condition for the multistationarity of chemical reaction networks. Bulletin of Mathematical Biology, Springer Verlag, 2013, 75 (11) Abstract Biochemical reaction networks grow bigger and bigger, fed by the high-throughput data provided by biologists and bred in open repositories of models allowing merging and evolution. Nevertheless, since the available data is still very far from permitting the identification of the increasing number of kinetic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…for oscillations, e.g. for homeostasis) in different formalisms, and in particular for ODE systems in [43,39,40,41,42] and recently in [38] for the ODE semantics of non-linear reaction systems.…”
Section: Influence Graph Associated To a Well-formed Reaction Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…for oscillations, e.g. for homeostasis) in different formalisms, and in particular for ODE systems in [43,39,40,41,42] and recently in [38] for the ODE semantics of non-linear reaction systems.…”
Section: Influence Graph Associated To a Well-formed Reaction Systemmentioning
confidence: 99%
“…However, Thomas's original condition provides no information in presence of reactions with two reactants, since a reaction like for instance A + B −→ C immediately creates a positive circuit of negative influences between A and B in the associated SIG and DIG for any reasonable kinetics. This counter-example has been recently rule out in [38], where it is shown that Thomas's conditions can be made stronger for reactions models, by labeling the influence edges by the reactions they come from, and by restricting the analysis of circuits to circuits labeled by different reactions. With this stronger condition for multi-stationarity, the analysis of labeled circuits in the DIG of a reaction system does provide information on its capabilities of exhibiting multi-stationarity.…”
Section: Influence Graph Associated To a Well-formed Reaction Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we are looking for a common generalization of [16] and [22]. We state this as a conjecture about chemical reaction networks (Conjecture 1).…”
Section: Introductionmentioning
confidence: 99%
“…In Section 3, following [22], [6] and [24], we introduce the reaction labelled influence graph of a chemical reaction network, and we use it to formulate the main result of [22], with three important corollaries. Next, we state the main result of [16] (Theorem 2).…”
Section: Introductionmentioning
confidence: 99%